The Effect of The Geogebra-Assisted Problem Based Learning Model on Problem Solving Ability and Critical Thinking Ability for Class X Students of SMA Negeri I Petang - Setiawi, Agustina Purnami (Universitas Negeri Makassar, 2021)
This study aimed to know the differences and to describe the ability of problem solving and critical thinking skills of students who engaged in Problem Based Learning with geogebra with students who took conventional learning. This research was a quasi-experimental study using post-test only control group design. The population of this research is the tenth grade students of SMA Negeri I Petang academic year of 2019/2020. There were 366 students in class X of SMA Negeri I Petang and were divided into eleven classes. In this study, the sample used were 65 students who were divided into two classes (experimental and control classes). The sample was determined by cluster random sampling technique. The research instruments were in the form of problem solving skills and mathematical critical thinking tests. The data obtained were analyzed using MANOVA test. The results of the analysis showed that the studentsâ€™ ability in solving problems and thinking critically using Problem Based Learning model assisted with geogebra was better than those who took conventional learning (F = 1917,095 and Sig. = 0,000; Ï <0.05)Â